2001
DOI: 10.1093/pasj/53.6.l45
|View full text |Cite
|
Sign up to set email alerts
|

First Results of a CO Survey of the Small Magellanic Cloud with NANTEN

Abstract: We present the first results from a new 12CO ($J = 1 \hbox{--} 0$) survey of the Small Magellanic Cloud (SMC) with the NANTEN millimeter-wave telescope. The survey covered the northeast and southwest regions of the main Bar, and the H ii regions N 84, N 88 in the Wing at a linear resolution of $\sim 50 \,\mathrm{pc}$. Twenty-one giant molecular clouds (GMCs), whose masses are $\sim 10^{4} \hbox{--} 10^{6} \,{{{M}_{\odot}}}$, were identified. Significant CO emission, $T_\mathrm{R}^{\ast} \sim 0.36 \,\mathrm{K}$… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
156
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(169 citation statements)
references
References 18 publications
12
156
1
Order By: Relevance
“…Mizuno et al (2001a) find that young emission objects are positionally well correlated with CO clouds, while emissionless objects of ages ∼6−100 Myr do not show any correlation to the CO clouds. Emission objects were excluded from our sample, so we cannot investigate their possible association with CO clouds.…”
Section: Spatial Age Distribution Smcmentioning
confidence: 73%
“…Mizuno et al (2001a) find that young emission objects are positionally well correlated with CO clouds, while emissionless objects of ages ∼6−100 Myr do not show any correlation to the CO clouds. Emission objects were excluded from our sample, so we cannot investigate their possible association with CO clouds.…”
Section: Spatial Age Distribution Smcmentioning
confidence: 73%
“…Under this assumption, based on early CO(1−0) observations with the CTIO/Columbia mm telescope and the SEST, Rubio et al (1993) found X SMC to be size dependent and equal to 3.9 × (R/10 pc) −0.7 X Gal where R is the cloud radius, defined as √ (A/π). The SMC NANTEN survey (Mizuno et al 2001), with a linear resolution of 40 pc, found consistently an average conversion factor X SMC ∼ 9X Gal . The CO(1−0) luminosity of SMCB1-1 is 1.2 × 10 3 K km s −1 (Rubio et al 1996) which multiplied by the appropriate X factor gives M(H 2 ) co = 2.7 × 10 4 M in Table 1.…”
Section: Gas Massmentioning
confidence: 88%
“…Recent studies of Local Group galaxies have surveyed large numbers of molecular clouds in the Large Magellanic Cloud (Mizuno et al 2001b), the Small Magellanic Cloud (Mizuno et al 2001a), M33 , and a bevy of Local Group dwarf galaxies (e.g., Wilson 1994;Taylor et al 1999). These recent studies explore the nature of star formation on galactic scales by studying the properties of giant molecular clouds (GMCs, M > 10 5 M ) throughout their host galaxies.…”
Section: Introductionmentioning
confidence: 99%